Bulgaria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper examines corporate productivity growth in Bulgaria using firm-level data. Firms with a higher share of innovative assets and lower financial distress are estimated to have higher productivity growth. Foreign, larger, and younger firms and firms in the tradable sectors also generally had faster productivity growth. The convergence of productivity to frontier firms may have slowed after the global financial crisis for existing firms. The evidence points to technological convergence for both total factor productivity and labor productivity to industry leaders. The result is robust with the coefficient statistically significant at the 1 percent level in all specifications. Policies that support R and D and innovation, improve business environment, and reduce debt service burden could potentially help raise productivity growth. Bulgaria's R and D spending lags behind other EU countries and there is ample room for improvement. A better business environment supported by stronger institutions could help improve company's profitability and financial health, raise investment, and attract more foreign direct investment, all conducive to raising productivity growth.